2014
DOI: 10.1038/ncomms4208
|View full text |Cite
|
Sign up to set email alerts
|

Solar-induced direct biomass-to-electricity hybrid fuel cell using polyoxometalates as photocatalyst and charge carrier

Abstract: The current polymer-exchange membrane fuel cell technology cannot directly use biomass as fuel. Here we present a solar-induced hybrid fuel cell that is directly powered with natural polymeric biomasses, such as starch, cellulose, lignin, and even switchgrass and wood powders. The fuel cell uses polyoxometalates as the photocatalyst and charge carrier to generate electricity at low temperature. This solar-induced hybrid fuel cell combines some features of solar cells, fuel cells and redox flow batteries. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
118
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 43 publications
2
118
1
Order By: Relevance
“…[24] It was reported that POMs are not only strong photo-oxidizing compounds but also strong Brønsted acid, so the biomass can be oxidized by POMs in solution under solar irradiation. [25] A variety of supported POMs, such as POMs/TiO 2 [26], POMs/MOFs [27], carbon quantum dots/silver nanoparticles/POMs [28], and POMs/organosilca frameworks [29], have been prepared for photocatalytic reactions. It would be very interesting to incorporate POMs onto the emerging 2D-structured, metal-free, visible light photocatalyst of g-C 3 N 4 , however, no such materials have been synthesized and tested for photodegradation of phenolics and dyes.…”
Section: Introductionmentioning
confidence: 99%
“…[24] It was reported that POMs are not only strong photo-oxidizing compounds but also strong Brønsted acid, so the biomass can be oxidized by POMs in solution under solar irradiation. [25] A variety of supported POMs, such as POMs/TiO 2 [26], POMs/MOFs [27], carbon quantum dots/silver nanoparticles/POMs [28], and POMs/organosilca frameworks [29], have been prepared for photocatalytic reactions. It would be very interesting to incorporate POMs onto the emerging 2D-structured, metal-free, visible light photocatalyst of g-C 3 N 4 , however, no such materials have been synthesized and tested for photodegradation of phenolics and dyes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an intermediate-temperature (75‒250 °C) fuel cell using phosphoric acid as catalyst can convert wood sawdust and pulp to carbon dioxide with output power density of 10 mW/cm 2   11 . Alternatively, a novel liquid catalyzed fuel cell (LCFC) was also proposed with the assistance of polyoxymetalates (POMs) 12 , and it performed well in generating electricity with nature polymeric biomasses 13, 14 . In fact, direct liquid redox fuel cells have been investigated in 2008 as an improvement to direct methanol fuel cells for numbers of advantages 15, 16 .…”
Section: Introductionmentioning
confidence: 99%
“…POMs are fine catalysts for the oxidation of biomass and the hydrolysis of macromolecule organics 17 . With its help, starch and cellulose can be hydrolyzed to glucose and then oxidized to carbon dioxide in LCFCs 12, 13 . Moreover, unlike other fuel cells, LCFCs use POMs for homogeneous catalysis instead of loading noble metal catalysts and they are insensitive to most contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Therein, the biomass is oxidized by polyoxometalates to FA and consecutively to formaldehyde in an aqueous solution under solar irradiation applying very mild conditions avoiding thermal degradation. 11 The first study aiming at a selective synthesis of FA or formate salts from biomass was published in 2008 by Jin et al 12,13 Glucose, a model compound for carbohydrate biomass, was oxidised hydrothermally with hydrogen peroxide as the oxidant at temperatures between 473 K and 573 K in the presence of alkali hydroxide, which obtained FA in up to 75% yield. However, such high FA yields were only obtained at high alkali concentrations (1.2 M) and using over-stoichiometric use of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%